49.2k views
1 vote
What is the solution to this system of linear equations?

y-x = 6
y + x = -10
(-2,-8)
(-8.-2)
(6.-10)
(-10.6)

User Shaun Neal
by
5.8k points

2 Answers

2 votes

Answer:

The correct answer is A

Explanation:

User Mathwizurd
by
4.8k points
3 votes

Answer:

(-8, -2)

Explanation:

y-x = 6

y + x = -10

Add the two equations together to eliminate x

y-x = 6

y + x = -10

--------------------

2y = -4

Divide by 2

2y/2 = -4/2

y = -2

Now find x

y+x = -10

-2+x = -10

x = -8

User Vinodh Thiagarajan
by
5.3k points